2013
DOI: 10.3748/wjg.v19.i34.5598
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of esophageal cancer

Abstract: Esophageal cancer (EsC) is one of the least studied and deadliest cancers worldwide because of its extremely aggressive nature and poor survival rate. It ranks sixth among all cancers in mortality. In retrospective studies of EsC, smoking, hot tea drinking, red meat consumption, poor oral health, low intake of fresh fruit and vegetables, and low socioeconomic status have been associated with a higher risk of esophageal squamous cell carcinoma. Barrett's esophagus is clearly recognized as a risk factor for EsC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
766
1
22

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 903 publications
(802 citation statements)
references
References 71 publications
13
766
1
22
Order By: Relevance
“…15 Adenocarcinoma of the esophagus occurs in the distal esophagus approximately three-fourth of the time with Barrett's esophagus being the most frequent predisposing risk factor. 16 The chronic reflux of gastric acid and bile at gastroesophageal junction and subsequent damage to esophagus has been implicated in the pathogenesis of Barrett's metaplasia (Figure 4). In present study, out of 101 cases, 47 cases of esophageal cancer comprising 46.5% were seen in fifth and sixth decade of life.…”
Section: Discussionmentioning
confidence: 99%
“…15 Adenocarcinoma of the esophagus occurs in the distal esophagus approximately three-fourth of the time with Barrett's esophagus being the most frequent predisposing risk factor. 16 The chronic reflux of gastric acid and bile at gastroesophageal junction and subsequent damage to esophagus has been implicated in the pathogenesis of Barrett's metaplasia (Figure 4). In present study, out of 101 cases, 47 cases of esophageal cancer comprising 46.5% were seen in fifth and sixth decade of life.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, taking the variation in epidemiology of EC, especially in developing countries, serious budgetary constraints and competition with the demands of other endemic diseases, cancer control programmes need to make wise choices to maximise the efficacy of any therapeutic or preventive measures [22].…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco and alcohol consumption are the predominant risk factors for ESCC (6,7). In addition, accumulating epidemiological studies indicated an association between obesity and EC (2,(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal cancer (EC) is a lethal disease that presents a global health threat to humans (1) particularly in developing countries, including China (2). A major histological subtype of EC is esophageal squamous cell carcinoma (ESCC) (3).…”
Section: Introductionmentioning
confidence: 99%